'I didn't mean that: It was just a slip of the tongue': Racial slips and gaffes in the public arena. (4th August 2017) - Burford‐Rice, Rose; Augoustinos, Martha
Abstract : Speech errors, slips, and gaffes made in the public arena that are perceived to be either implicitly or explicitly racially offensive often result in significant social consequences to the responsible speaker and generate public controversy. The current research, informed by conversation analysis and discursive psychology, examines how speakers manage such troubles‐in‐speaking in public settings. The sample of naturalistic data includes five such instances and related apologies sourced from YouTube and news websites. The analysis examined how speakers initiated repairs when making offensive racial slips and gaffes and followed these up with apologies. Self‐detected transgressions were repaired in fewer turns than other‐detected blunders. Speakers accounted for their transgressions as innocent mishaps (e.g., 'it was just a slip of the tongue', 'an honest mistake') to fend off attributions of prejudice or a racist identity. Thus, a common resource that speakers drew upon to exonerate themselves was that what they said, did not align with their psychological intentions. Intention then was a notable psychological resource for denying and fending off attributions of prejudice. Follow‐up apologies were related organizationally and worked to either address or decrease the likelihood of dispreferred responses from the public/audience. These apologies included the use of affect, graduation, amplification, and judgements of capacity. Although this research does not address the possible psychological nature of racial slips and gaffes – the question of what they really mean – their occurrence in everyday life and institutional settings suggest that their repressive qualities reflect shared patterns of understanding in societies structured by racial inequality.